PERAN MEDIASI PERILAKU PELANGGAN DALAM HUBUNGAN RETARGETING ADVERTISING DAN PRICE DISCOUNT TERHADAP KEPUTUSAN PEMBELIAN DI BERRYBENKA - Rahma Novia Ningrum; Shinta Rahmani (Universitas Mercu Buana, 2023)
This study aims to examine and analyze the Mediation Role of Customer Behavior in Retargeting Advertising and Price Discounts on Purchase Decisions at Berrybenka. This research data is data taken from secondary data of various kinds of literature in the form of literature reviews, books, previous research and previous research hypotheses and primary data obtained from processing questionnaire data filled out by consumers who have visited and made purchases on the Berrybenka web-app. The number of samples used is 144 respondent and the analytical technique used in this study is to use Partial Least Square (PLS) analysis. The findings of previous studies indicate that Retargeting Advertising, Price Discounts and Customer Behavior have a positive and significant effect on Purchase Decisions.